Characterization of the influence of Mansonella perstans co-infection on immunity - Azonvide, Codjo Laurent; Adjobimey, Tomabu; SINA OROU, S. M. ABDEL HAZIZ; BABA-MOUSSA, LAMINE SAÏD (My University, 2022)
The study aimed to characterize the influence of Mansonella perstans co-infection on immunity. This research was carried out in November, 2021 in the neighboring villages of Saint Camille de Davougon in the Abomey Commune. Blood samples were collected from both genders of all ages. Buruli ulcer was diagnosed by polymerase chain reaction (PCR), using specific IS2404 repeat sequence for Mycobacterium ulcerans. Microfilaria detection was done with the help of the counting chamber technique. Using 100 white blood cells, the proportion of eosinophils was determined. Minividas® Biomerieux was used to quantify the IgE titers in the patients' serum using an immuno-enzymatic sandwich enzyme linked immunosorbent assay (ELISA). This study shows an overall co-infection of Buruli ulcers with M. perstans as 23.86%. In the age group of fewer than 16 years, the co-infection prevalence was 28.57% (n=6), while in patients of age greater than 16, the co-infection prevalence was 71.42% (n=15). The Buruli ulcer patients co-infected with M. perstans had the highest median eosinophil level, whereas the control group had the lowest. The lowest median total IgE titer was observed in the control, while the maximum was observed in the Buruli ulcer patients co-infected with M. perstans. This study concludes that Buruli ulcer co-infection with M. perstans prevails in some rural villages in Benin. Therefore, this pathogen must be considered in the treatment of Buruli ulcer. The findings imply that IgE could be used to assess the patient's immunological response during Buruli ulcer and M. perstans.
Keywords: Mansonella perstans; co-infection; immunity; Buruli ulcer.